2014
DOI: 10.1111/vcp.12215
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocytosis in nonanemic dogs: increasing prevalence and potential etiologies

Abstract: Prevalence of RAA has increased in recent years in our canine population. More ubiquitous use of anti-inflammatory medications and nutraceuticals, associated with increased diagnosis of osteoarthritis should be considered as contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…non‐steroidal anti‐inflammatory drugs (NSAIDs), glucocorticoids] were identified (Pattullo et al . ). NSAIDs can induce gastrointestinal bleeding (Vollmar , Monteiro‐Steagall et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…non‐steroidal anti‐inflammatory drugs (NSAIDs), glucocorticoids] were identified (Pattullo et al . ). NSAIDs can induce gastrointestinal bleeding (Vollmar , Monteiro‐Steagall et al .…”
Section: Introductionmentioning
confidence: 97%
“…While factors contributing to RWA in dogs were discussed in recent studies (Pattullo et al . ), there is little information available for cats. Thus, the aim of our retrospective multicentre study was to characterise the phenomenon of RWA in cats and dogs.…”
Section: Introductionmentioning
confidence: 99%
“…None of these risk factors were identified in this case; however, this syndrome was only recently identified, and the complete list of underlying etiologies has not yet been established. It should be noted that Pattullo et al found macrocytosis to be rare in a population of dogs with reticulocytosis in the absence of anemia …”
Section: Discussionmentioning
confidence: 96%
“…Recently, reticulocytosis in the absence of anemia was reported to be increasing in dogs and postulated to be due to chronic erythrocytic destruction, or loss . Potential causes included dietary supplementation with polyunsaturated fatty acids and zinc, administration of medications such as nonsteroidal anti‐inflammatories, glucosamine, and corticosteroids, and high‐intensity exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation